Techniques and Innovation in Hernia Surgery - Guttadauro, Angelo (IntechOpen, 2020)
Every year in the United States there are about 800 000 interventions for the treatment of hernias.New prosthetic materials, specific devices, and surgical techniques that are more attentive to patient well-being and patient compliance offer a new dimension to abdominal wall surgery . Surgery of the abdominal wall, once considered minor, has now acquired the interest of the scientific world.Today, many surgical procedure options are available for hernia pathology. The choice of the correct indication for the patient's pathology is very important for improving the effectiveness of surgery and ensuring better patient comfort, according to the concept of "tailored surgery". The aim of this book is to collect experiences that analyze the most used and innovative surgical techniques by evaluating the correct indications in order to obtain maximum patient comfort and the lowest number of complications.